IN VITRO ANTIOXIDANT STUDIES OF ETHANOLIC EXTRACT OF LEAVES OF BLUMEA MOLLIS - SREEDEVI ADIKAY; ANEESHA, A. (International Journal of Pharma and Bio Sciences, 2012)
The antioxidant activity of defatted ethanolic extract of the leaves of Blumea mollis were studied for its free radical scavenging property on different in vitro antioxidant models like DPPH radical, hydroxyl radical, nitric oxide radical scavenging activity, reducing power, superoxide anion radical scavenging activity were analyzed. The extract showed free radical scavenging property in dose-dependent manner